Functional outcome of operatively treated displaced intra-articular calcaneal fractures using two parallel contoured reconstruction plates - Lakhey, S; Manandhar, RR; Pradhan, RL; Pandey, BK; Sharma, S; Rijal, KP (Kathmandu University Medical Journal, 2010)
Introduction: The treatment of displaced intra-articular calcaneal fracture is controversial. Conventionally, they were treated non-operatively. However, some surgeons are now operatively treating these fractures because of continuing dissatisfaction with the outcome of conservative treatment of these fractures and improvements that have occurred in surgical techniques and complication rates. Objective: The aim of this study was to determine the functional outcome of operatively treated displaced intra-articular calcaneal fractures using two parallel contoured reconstruction plates. Materials and methods: 12 patients with 14 displaced intra-articular calcaneal fractures involving the subtalar joint were included in the study conducted between July 2005 and December 2008. The fracture site was exposed using extended lateral approach. Internal fixation was done by two nearly parallel 3.5mm reconstruction plates and screws contoured to form a gentle curve in all cases with the first plate fixed just below the articular surface. At the end of follow up, the patients' foot function was assessed by Calcaneal Fracture Scoring System of Kerr et al. Patients were also enquired about their satisfaction with their treatment outcome. Results: The patients were followed up for duration of 12 to 24 months (mean 15.64 months). The outcome score as measured by Calcaneal Fracture Scoring System ranged from 48 to 94 (mean 83.64). 11 of 12 patients (91.6 %) were satisfied with the treatment. Conclusion: Displaced intra-articular fractures treated by open reduction and internal fixation, using two nearly parallel, contoured reconstruction plates through an extensile lateral approach and following the principles of treatment of intraarticular fractures, have good functional results with high patient satisfaction rate. Key words: displaced intra-articular calcaneal fractures; operative treatment. DOI: 10.3126/kumj.v8i1.3215 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 12-17